STUDI PEMETAAN MULTI-DRUG RESISTANT (MDR) ESCHERICHIA COLI PADA PETERNAKAN BABI DI KOTA KUPANG - Novallino Kallau; I Wayan Teguh Wibawan; Denny Widaya Lukman; Mirnawati Baharudin Sudarwanto (JURNAL KAJIAN VETERINER, 2019)
The aim of this study was to determine the pattern of the spread of antibiotic-resistant E. coli on pig farms in Kupang City by using mapping analysis. Data on E. coli resistance comes from the results of laboratory analysis and as secondary data for spatial analysis. Spatial analysis uses the nearest neighbour index, convex hull and elementary analysis of disease methods. The results of this study have shown a high prevalence of E. coli (85.4%) with clustered distribution patterns and have a wide spread (10920 ha) in the area in Kupang City. MDR E. coli had a moderate prevalence (57.31%) by forming a group spread pattern and a wide spread (7778 Ha) on pig farms in Kupang City. This result encourages prevention and control efforts by all interested parties so that the rate of spread of resistant E. coli can be reduced.